Analisis Rasio Efektivitas, Efisiensi, dan Desentralisasi untuk Mengukur Kinerja Keuangan Lombok Timur - Novia Romdani; Fatimah, Siti; Purwadinata, Subhan (Pusat Riset dan Inovasi Nasional, 2025)
Is a challenge that must be accepted by the government in order to develop and manage their respective regions properly. This study aims to analyze the financial performance of East Lombok Regency from 2018 to 2023, focusing on three ratios: 1. Regional Original Revenue (PAD) Effectiveness Ratio, 2. Regional Financial Efficiency Ratio, and 3. Fiscal Decentralization Degree Ratio. The results of the analysis show that the financial performance of East Lombok Regency based on: 1. The PAD Effectiveness Ratio can be categorized as less effective, with an average effectiveness of 90.04%, 2. The Regional Financial Efficiency Ratio is classified as inefficient, because the average of this ratio reaches 101.03%, and 3. The Fiscal Decentralization Degree Ratio is also considered insufficient, with an average of 12.24%.